2016
DOI: 10.15366/rimcafd2016.61.003
|View full text |Cite
|
Sign up to set email alerts
|

Efecto ergogénico de la ingesta de fosfato sódico en sujetos físicamente activos / Ergogenic Effect of Sodium Phosphate Intake in Physically Active Subjects

Abstract: RESUMENEste estudio pretende evaluar los efectos de la ingesta de fosfato sódico a corto plazo, sobre la composición corporal, serie roja y parámetros ergoespirométricos máximos y submáximos. A una muestra de 20 sujetos físicamente activos, separados en dos grupos, se les suministró fosfato sódico durante 7 días (50 mg/kg masa magra) o placebo. Ambos grupos realizaron una prueba de esfuerzo incremental máxima en cicloergómetro, siguiendo el

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In our study, we did not observe any significant changes in VO 2 and RER during exercise at a given workload. Similarly, no significant decrease in submaximal RER or VO 2 after phosphate loading was reported in studies conducted under normoxic conditions [10,38,44,69]. Our findings suggest that phosphate salts did not shift the use of metabolic substrates towards fat utilization and did not reduce the energy cost of exercise at an intensity > 60% of VO 2max in hypoxic conditions.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…In our study, we did not observe any significant changes in VO 2 and RER during exercise at a given workload. Similarly, no significant decrease in submaximal RER or VO 2 after phosphate loading was reported in studies conducted under normoxic conditions [10,38,44,69]. Our findings suggest that phosphate salts did not shift the use of metabolic substrates towards fat utilization and did not reduce the energy cost of exercise at an intensity > 60% of VO 2max in hypoxic conditions.…”
Section: Discussionsupporting
confidence: 50%
“…Our findings suggest that phosphate salts did not shift the use of metabolic substrates towards fat utilization and did not reduce the energy cost of exercise at an intensity > 60% of VO 2max in hypoxic conditions. Interestingly, Marcos et al [38] found that SP ingested for seven days at a dose of 50 mg/kg lean body mass improved energy efficiency at low exercise intensity, where the major metabolic substrate for energy production is fat oxidation. It should be noted that efficiency in their study was calculated for a lower exercise intensity than in our experiment, which may be reflected by the differences in RER (0.82-0.86 vs. 0.93-0.98).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations